Monetary and Fiscal Policy in a World of Capital Mobility: A Respecification - Tower, Edward (Review of Economic Studies, 1972)
Journal Article Monetary and Fiscal Policy in a World of Capital Mobility: a Respecification Get access Edward Tower Edward Tower University of Auckland Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 39, Issue 3, July 1972, Pages 251–262, https://doi.org/10.2307/2296357 Published: 01 July 1972 Article history Received: 01 July 1970 Revision received: 01 October 1971 Published: 01 July 1972